1989
DOI: 10.1073/pnas.86.10.3629
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of regulation of the 422(aP2) gene by cAMP during preadipocyte differentiation.

Abstract: During differentiation of 3T3-L1 preadipocytes into adipocytes, expression of the gene encoding adipocyte 422(aP2) protein is activated. We have shown that the first 248 base pairs of the 422(aP2) gene promoter (which lacks a consensus cAMP response element) are sufficient to confer inducibility of a reporter gene by cAMP in preadipocytes. We now demonstrate by deletion analysis that this DNA segment contains overlapping negative and positive regulatory elements. The positive regulatory element contains a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 38 publications
1
52
0
Order By: Relevance
“…Afabp mRNA and protein production are significantly induced during adipocyte differentiation [7]. AFABP has frequently been used as an adipocyte differentiation marker [8][9][10], based on these observations. The DNA-binding protein CCAAT/enhancerbinding protein interacts with the AFABP promoter and elevates expression of the AFABP gene [11].…”
Section: Production and Structure Of Afabpmentioning
confidence: 99%
See 1 more Smart Citation
“…Afabp mRNA and protein production are significantly induced during adipocyte differentiation [7]. AFABP has frequently been used as an adipocyte differentiation marker [8][9][10], based on these observations. The DNA-binding protein CCAAT/enhancerbinding protein interacts with the AFABP promoter and elevates expression of the AFABP gene [11].…”
Section: Production and Structure Of Afabpmentioning
confidence: 99%
“…The DNA-binding protein CCAAT/enhancerbinding protein interacts with the AFABP promoter and elevates expression of the AFABP gene [11]. Furthermore, cyclic adenosine monophosphate induces AFABP gene expression during adipocyte differentiation by relieving the inhibitory effect of a negative regulatory element in the AFABP promoter [10]. Moreover, insulin-sensitising and pro-adipogenic peroxisome proliferator-activated receptor (PPAR)γ agonists induce AFABP production and secretion [12,13].…”
Section: Production and Structure Of Afabpmentioning
confidence: 99%
“…These results, taken together with those described above, indicate that the differentiation-specific factor is C/EBP. Moreover, the sites at which C/EBP (and nuclear extracts from differentiated 3T3-L1 adipocytes) interacts with the 422(aP2) and SCDl promoters are within the regions that have been shown to be essential for the activation of both genes during preadipocyte differentiation (Distel et al 1987;Ntambi et al 1988;Yang et al 1989). …”
Section: •••••• -*-422(ap2)mentioning
confidence: 99%
“…Transfection experiments with chimeric 422(aP2) promoter-CAT constructs show that the gene is activated by glucocorticoid and cAMP (Cook et al 1988;Yang et al 1989), two agents used to induce differentiation of 3T3-L1 preadipocytes. It has been demonstrated that the first 168 bp of the 5'-flanking sequence of this gene are sufficient for differentiation-dependent expression in 3T3-442A preadipocytes [Distel et al 1987).…”
mentioning
confidence: 99%
See 1 more Smart Citation